Upaya Peningkatan Kepatuhan Konsumsi Tablet Tambah Darah sebagai Pencegahan Anemia pada Remaja Putri di SMP Islam Nurul Ihsan Palangka Raya - Tisha Patricia; Permatasari, Silvani; Eka Shinta, Herlina (Jurnal Pengabdian Kampus, 2025)
Anemia is one of the six nutritional problems that exist in Indonesia today. Anemia often occurs, especially in adolescence. Globally, around 600 million preschool and school-aged children suffer from anemia. Later in life, adolescent girls who are anemic are at risk of anemia when they become pregnant women, which can cause complications in pregnancy and childbirth as well as death of the mother and child. The most complete data on Fe provision reports was reported by Central Kalimantan province in Pahandut sub-district in 2022, which includes junior high schools (SMP), one of which is SMP Islam Nurul Ihsan, Palangka Raya. However, there is no data on compliance with taking blood supplement tablets which are often given by the Puskesmas Pahandut to young women and their hemoglobin levels. The aim of this activity is to collaborate with the Puskesmas Pahandut to provide education to increase compliance with taking blood supplement tablets in an effort to prevent anemia and provide hemoglobin level checks for young women. This community service activity was attended by 30 grade 7 junior high school students who had never taken Fe tablets and had menstruated. The service implementation activity in the form of an effort to increase compliance with the consumption of blood supplement tablets as a prevention of anemia in young women at SMP Islam Nurul Ihsan Palangka Raya was successfully carried out, the participants enthusiastically listened to the material presented. Students who experienced anemia before being given blood supplement tablets were 30% while after being given the tablets added blood decreased to 13.3%. Students who adhere to taking tablets increase blood by 60%. Factors that influence compliance in taking blood supplement tablets include: knowledge, attitude, motivation, parental support and teacher support.